O-072 Markers of cardiometabolic health of adolescents conceived through assisted reproductive technologies (ART) appear reassuring. (6th August 2021) - Wijs, L; Doherty, D; Keelan, J; Burton, P; Yovich, J; Beilin, L; Mori, T; Huang, R C; Adams, L; Olynyk, J; Ayonrinde, O; Hart, R
Abstract: Study question: Is the cardiometabolic health of adolescents conceived through ART worse than that of their spontaneously-conceived counterparts? Summary answer: The majority of cardiometabolic and vascular health parameters of ART-conceived adolescents are more favourable than those of their spontaneously-conceived counterparts of similar age. What is known already: It has been proposed that ART induces epigenetic alterations during embryonic development which could lead to cardiometabolic disease later in life. However, individuals requiring ART may themselves be metabolically less healthy than the general population, which could lead to a genetically increased risk of cardiometabolic disorders in the offspring, rather than the ART procedure. The literature pertaining to cardiometabolic health of ART-conceived offspring is contradictory, but generally suggests unfavourable cardiometabolic health parameters. With over 8 million children and adults born through ART worldwide, it is imperative to investigate whether early signs of adverse cardiometabolic differences persist into adolescence and beyond. Study design, size, duration: The Growing Up Healthy Study (GUHS) is a prospective study that recruited 303 ART-conceived adolescents, born 1991-2001 in Western Australia. Their health parameters, including cardiometabolic factors, were assessed and compared with spontaneously conceived counterparts of similar socioeconomic background and age from the Raine Study Generation 2 (Gen2). The 2868 Gen2 participants were born 1989-1992 and are representative of the Western Australian adolescent population. At age 16-17 (2013-2017), GUHS participants replicated assessments previously completed by Gen2. Participants/materials, setting, methods: Cardiometabolic parameters were compared between 165 GUHS (male = 50.9%) and 1690 Gen2 (male = 49.8%) adolescents. Assessments consisted of a detailed questionnaire; health and demographic parameters, anthropometric assessments; height, weight, body-mass index (BMI), waist circumference and skinfold thickness, fasting serum biochemistry, arterial stiffness and blood pressure assessment using applanation tonometry, assessment of non-alcoholic fatty liver (NAFLD) and thickness of abdominal fat compartments using ultrasonography. Chi 2, Fisher's Exact and Mann-Whitney U tests, performed in SPSS V25, examined cohort differences. Main results and the role of chance: GUHS adolescents appeared to be healthier from a cardiometabolic perspective than their Gen2 counterparts. They were leaner, with lower BMI (median: 21.23 vs. 22.06, P = 0.004), lower waist circumference (median: 74.10 vs. 76.75 cm, P = 0.031), and thinner skinfolds (triceps median: 12.1 vs. 14.0 mm, P = 0.019, subscapular median: 10.6 vs. 11.9 mm, P < .001, mid-abdominal median: 16.0 vs. 19.9 mm, P < 0.001, supraspinal median: 10.7 vs. 13.5 mm, P < 0.001). No significant differences were detected in the following serum fasting parameters: glucose, insulin, HOMA-IR, LDL cholesterol, total cholesterol, cholesterol/HDL-ratio, triglycerides, CRP and ALT. HDL cholesterol levels were more favourable in GUHS (P < 0.001). NAFLD was present in 10.9% of GUHS vs. 15.2% of Gen2 adolescents (P = 0.174), with no difference in steatosis severity score (P = 0.309). ART offspring had less subcutaneous adipose tissue (median: 8.0 vs. 14.0 mm, P < .001), more visceral adipose tissue (median: 40.0 vs. 32.0 mm, P < 0.001), with no difference in pre-peritoneal adipose tissue (P = 0.087). Measures of arterial stiffness were lower in GUHS. Pulse wave velocity: median 6.1 vs. 6.4 m/s, P < 0.001 and heart rate corrected augmentation index: median -10.25 vs. -8.00, P = 0.006. No significant differences in blood pressure or heart rate were detected. Stratification by sex did not greatly alter the results. Limitations, reasons for caution: Despite the substantial study size and the unique study design, we were unable to differentiate between different types of ART (e.g. IVF vs. ICSI), draw definite conclusions or relate outcomes to cause of infertility. Given the observational character of this study, causation cannot be proven. Wider implications of the findings: In this study we did not detect any adverse effect of ART on cardiometabolic health at adolescence, in contrast to some studies. Given the lack of consensus, future well-designed and appropriately-powered studies are necessary to investigate cardiometabolic health in ART adults. Trial registration number: not applicable